2017
DOI: 10.1177/1475921717694812
|View full text |Cite
|
Sign up to set email alerts
|

Use of an elasto-plastic model and strain measurements of embedded fibre Bragg grating sensors to detect Mode I delamination crack propagation in woven cloth (0/90) composite materials

Abstract: Mode I fracture analysis being employed to study delamination damage in fibre-reinforced composite structures under in-plane and out-of-plane load applications. However, due to the significantly low yield strength of the matrix material and the infinitesimal thickness of the interface matrix layer, the actual delamination process can be assumed as a partially plastic process (elasto-plastic). A simple elasto-plastic model based on the strain field in the vicinity of the crack front was developed for Mode I cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, as shown in Figure 3(d), the GFR SMPC with photothermal fillers has demonstrated improved aspects of fibre bonding and adhesion between fibre and matrix. Under loaded circumstances, the poor bonding between the fibre and matrix will cause local bending to propagate microdelamination until the failure (Herath et al, 2018;Kakei et al, 2017). Accordingly, the GFR SMPCs with photothermal fillers have a less possibility for a delamination failure while operating with loads.…”
Section: Resultsmentioning
confidence: 99%
“…However, as shown in Figure 3(d), the GFR SMPC with photothermal fillers has demonstrated improved aspects of fibre bonding and adhesion between fibre and matrix. Under loaded circumstances, the poor bonding between the fibre and matrix will cause local bending to propagate microdelamination until the failure (Herath et al, 2018;Kakei et al, 2017). Accordingly, the GFR SMPCs with photothermal fillers have a less possibility for a delamination failure while operating with loads.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that both stress-strain curves tensile and compressive, present a non-linear trend. Such behaviour can occur due to voids between laminae and progressive failures of fibres due to local bending at void locations [16]. The impact energy absorbance of the SMPC is shown in Figure 7 (c).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…13,20 Optical fibers are another practical method that provides strain measurement for crack monitoring in adhesive joints. The most common fiber optic systems are fiber Bragg gratings (FBG), 21,22 chirped FBG (CFBG), 23 and optical backscatter reflectometry (OBR). 24 Unlike FBG and CFBG, OBR offers distributed strain sensing over long distances.…”
Section: Introductionmentioning
confidence: 99%